Enhancing the Awareness Level on Phishing Attacks Among Malaysians: Analysis and Recommendations - Mohd Sarifuddin, Othman@Mustafa; Rahman, Md. Arafatur; M. Nomani, Kabir; Kamal Z., Zamli (American Scientific Publisher, 2018)
This paper presents an analysis of awareness level on phishing attack among Malaysians. Phishing and fraudster activities have been important issues in Malaysia. The methodology involves the questionnaires which are distributed and answers were collected and recorded as random samples. Next, statistical data were analyzed and categorized into different parts for enhanced knowledge and experience in data exploration. The test results related to hypothesis tests are provided. Using this analysis, influence of source problem and weakness of victims are revealed in order to mitigate the issue. Based on this, recommendations have been provided to encounter the issues.